Characterization of the FtsZ C-Terminal Variable (CTV) Region in Z-Ring Assembly and Interaction with the Z-Ring Stabilizer ZapD in E. coli Cytokinesis. - Kuo-Hsiang Huang (PLoS ONE, 2016)
Polymerization of a ring-like cytoskeletal structure, the Z-ring, at midcell is a highly conserved feature in virtually all bacteria. The Z-ring is composed of short protofilaments of the tubulin homolog FtsZ, randomly arranged and held together through lateral interactions. In vitro, lateral associations between FtsZ protofilaments are stabilized by crowding agents, high concentrations of divalent cations, or in some cases, low pH. In vivo, the last 4-10 amino acid residues at the C-terminus of FtsZ (the C-terminal variable region, CTV) have been implicated in mediating lateral associations between FtsZ protofilaments through charge shielding. Multiple Z-ring associated proteins (Zaps), also promote lateral interactions between FtsZ protofilaments to stabilize the FtsZ ring in vivo. Here we characterize the complementary role/s of the CTV of E. coli FtsZ and the FtsZ-ring stabilizing protein ZapD, in FtsZ assembly. We show that the net charge of the FtsZ CTV not only affects FtsZ protofilament bundling, confirming earlier observations, but likely also the length of the FtsZ protofilaments in vitro. The CTV residues also have important consequences for Z-ring assembly and interaction with ZapD in the cell. ZapD requires the FtsZ CTV region for interaction with FtsZ in vitro and for localization to midcell in vivo. Our data suggest a mechanism in which the CTV residues, particularly K380, facilitate a conformation for the conserved carboxy-terminal residues in FtsZ, that lie immediately N-terminal to the CTV, to enable optimal contact with ZapD. Further, phylogenetic analyses suggest a correlation between the nature of FtsZ CTV residues and the presence of ZapD in the β- γ-proteobacterial species.